Anorexia and nervous bulimia trough the Rorschach Psycodiagnosis - Fernández Bravo, Friedda (2008)
An exploratory descriptive research. The sample is purposive and referred from  psychiatrist´s offices five patients. They are outpatients and all of them have as precedent 2 years from the beginning of the symptoms. The instruments applieda were the Rorschach psychodiagnostics and the Millon Clinic  Multiaxial Inventory MCMI-II The structural summaries are analyzed, constellations are compared and contents are analyzed from a dynamic point of view.